2020
DOI: 10.1038/s41598-020-61208-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Molecular Characterization of liver-enriched gene 1

Abstract: Liver-enriched gene 1 (Leg1) is a newly identified gene with little available functional information. To evolutionarily and molecularly characterize Leg1 genes, a phylogenetic study was first conducted, which indicated that Leg1 is a conserved gene that exists from bacteria to mammals. During the evolution of mammals, Leg1s underwent tandem duplications, which gave rise to Leg1a, Leg1b, and Leg1c clades. Analysis of the pig genome showed the presence of all three paralogs of pig Leg1 genes (pLeg1s), whereas on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 60 publications
3
11
0
Order By: Relevance
“…Our previous study suggested that mammalian LEG1 genes could be divided into three classes, LEG1a, LEG1b, and LEG1c [9]. Tandem duplication occurred first in the common ancestor of mammals, giving rise to the LEG1c and LEG1 branches.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study suggested that mammalian LEG1 genes could be divided into three classes, LEG1a, LEG1b, and LEG1c [9]. Tandem duplication occurred first in the common ancestor of mammals, giving rise to the LEG1c and LEG1 branches.…”
Section: Discussionmentioning
confidence: 99%
“…The pig LEG1 gene expression plasmids pCAG-pleg1a-3×FLAG, pCAG-pleg1b-3×HA, and pCAG-pleg1c-3×FLAG were constructed previously [9]. Using similar strategies, the pCAG-platypusMLP-3×FLAG plasmid was generated.…”
Section: Plasmid Preparationmentioning
confidence: 99%
See 3 more Smart Citations